2022
DOI: 10.3390/plants11192630
|View full text |Cite
|
Sign up to set email alerts
|

Three-Fluorophore FRET Enables the Analysis of Ternary Protein Association in Living Plant Cells

Abstract: Protein-protein interaction studies provide valuable insights into cellular signaling. Brassinosteroid (BR) signaling is initiated by the hormone-binding receptor Brassinosteroid Insensitive 1 (BRI1) and its co-receptor BRI1 Associated Kinase 1 (BAK1). BRI1 and BAK1 were shown to interact independently with the Receptor-Like Protein 44 (RLP44), which is implicated in BRI1/BAK1-dependent cell wall integrity perception. To demonstrate the proposed complex formation of BRI1, BAK1 and RLP44, we established three-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…to the loss of valuable information (Immink et al 2009;Denay et al 2019;Tonaco et al 2006;Immink et al 2002;Glockner et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…to the loss of valuable information (Immink et al 2009;Denay et al 2019;Tonaco et al 2006;Immink et al 2002;Glockner et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to BiFC, FRET assays have the advantage of having higher spatial resolution and, more importantly, are more specific, as complementing FP fragments show a tendency for self-assembly resulting in false positive interactions (Horstman et al 2014;Shyu and Hu 2008). FLIM in contrast to intensity-or spectral-based FRET methods, is more gentle on cells and tissues due to lower required laser intensity and is generally considered the more accurate method to detect FRET (Strotmann and Stahl 2022;Long et al 2017;Long et al 2018;Stahl et al 2013;Russinova et al 2004;Glockner et al 2022).…”
Section: Fret-flim Could Not Detect Mads-domain Protein Interactions ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of plant growth, the Arabidopsis PM-localized receptor kinase FERONIA has recently been shown to regulate pavement cell morphogenesis upon binding to highly dmPectin ( Lin et al., 2022 ). In Arabidopsis, the PM receptors BRASSINOSTEROID INSENSITIVE 1 (BRI1) and RECEPTOR-LIKE PROTEIN 44 (RLP44), together with the BRI1 co-receptor BRI1-Associated Kinase 1 (BAK1), have been reported to coordinately mediate plant responses to abnormally high levels of mPectin present at the cell wall ( Wolf et al., 2012 , 2014 ; Glöckner et al., 2022 ). Similarly, the WALL-ASSOCIATED KINASEs (WAKs) and WAK-likes (WAKLs) participate in controlling cell expansion ( Lally et al., 2001 ; Wagner and Kohorn, 2001 ; Wu et al., 2020 ; Li et al., 2021 ), presumably by sensing pectin perturbations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there can also be an energy transfer from the donor to the lowest-energy acceptor via the intermediate acceptor. Several recent studies have successfully demonstrated the development of single-molecule triple FRET techniques. However, the extension of FRET to triple FRET is not as straightforward as it appears, and there are many challenges that limit the quantitative analysis of triple FRET data, e.g., severe photobleaching, small absorption/emission spectral overlap, and large distances between multicolor fluorescent dyes.…”
Section: Introductionmentioning
confidence: 99%